10Be/9Be-based chronostratigraphy of ODP Hole 181-1121B from the Southwest Pacific Ocean - I J Graham; Robert M Carter; R G Ditchburn; A Zondervan (PANGAEA, 2004)
A 10Be/9Be-based chronostratigraphy has been determined for ODP 181, Site 1121 sediment core, recovered from the foot of the Campbell Plateau, Southwest Pacific Ocean. This core was drilled through the Campbell extquotesingleskin drift extquotesingle in ca. 4500 m water depth on the mid-western margin of the extensive Campbell Nodule Field, beneath the flow of the major cold-water Deep Western Boundary Current (DWBC). In the absence of detailed biostratigraphy, beryllium isotopes have provided essential time information to allow palaeo-environmental interpretation to be undertaken on the upper 7 m of the core. Measured 10Be/9Be ratios of sediment, and of ferromanganese nodules entrapped in the sediment, decrease systematically with depth in the core, in accordance with radioactive decay. However, the 10Be/9Be data diverge from ca. 3 m below the seafloor (mbsf) to the top of the core, giving rise to several possible geochronological models. The preferred model assumes that the measured 10Be/9Be ratios of the nodule rims reflect initial 10Be/9Be ratios equivalent to contemporary seawater, and that these can be used to derive the true age of the sediment where the nodules occur. The nodule rim ages can be then used to interpret the sediment 10Be/9Be data, which indicate an overall age to ca. 7 mbsf of ca. 17.5 Ma. The derived chronology is consistent with diatom biostratigraphy, which indicates an age of 2.2-3.6 Ma at 1 mbsf. Calculated sedimentation rates range from 8 to 95 cm m.y.**-1, with an overall rate to 7 mbsf of ca. 39 cm m.y.**-1. The lowest rates generally coincide with the occurrence of entrapped nodules, and reflect periods of increased bottom current flow causing net sediment loss. Growth rates of individual nodules decrease towards the top of the sediment core, similar to the observed decrease in growth rate from core to rim of seafloor nodules from the Campbell Nodule Field. This may be related to an overall increase in the vigour of the DWBC from ca. 10 Ma to the present.
Supplement to: Graham, IJ et al. (2004): Chronostratigraphy of ODP 181, Site 1121 sediment core (Southwest Pacific Ocean), using 10Be/9Be dating of entrapped ferromanganese nodules. Marine Geology, 205(1-4), 227-247, https://doi.org/10.1016/S0025-3227(04)00025-8